Urgensi Pendidikan Pranatal bagi Ibu Hamil - Miftahillah Miftahillah (Program Studi PGRA, 2016)
Urgency prenatal education for pregnant is less understood lack prenatal counseling their education, through counseling and its practice is expected of pregnant can increase the potential of the baby into multiple intelligences. The purpose of this research to know how the urgency of prenatal education for pregnant. The method of using library research that activity data collection methods literature, reading and recording and processing of materials research. Sources of primary data drawn directly from the source, in the form of all books related to prenatal education on all aspects of general and aspects of Islam. Descriptive data analysis is to describe and interpret what is there about the condition or relationship, the opinion is growing, the process is ongoing, results or effects occur or trends developing. And the period of content analysis departs from the axiom that the study of the process and content of communication is the basis of all social science. Conclusions education began selecting a mate. And prenatal education efforts made since the child in the womb until the child is born based on the Qur'an, hadith. Steps taken by pregnant to their intake are a) reading, memorizing, thinking and calculating; b) musical or singing or berqosidah or bersholawat or bertilawah Qur'an; c) Psychological, feelings and actions related to pregnant and her husband; d) communication and humor, pertaining to reduce stress in pregnant